2022
DOI: 10.1038/s41598-022-08424-5
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic, molecular and biochemical evaluation of somatic hybrids between Solanum tuberosum and S. bulbocastanum

Abstract: Somatic hybridization has been frequently used to overcome sexual incompatibility between potato and its secondary germplasm. The primary objective of this study was to produce and evaluate somatic hybrids of Solanum tuberosum (Stub) and S. bulbocastanum (Sblb) for breeding purposes. In 2007, 23 somatic hybrids were produced using an electrofusion of mesophyll protoplasts of diploid (2n = 2x = 24) potato line StubDH165 and S. bulbocastanum PI24351 (Sblb66). Phenotype of somatic hybrids in field conditions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…The methanolic extract of S. bulbocastanum leaves obtained by the UAE technique did not contain any Solanaceae -specific glycoalkaloids, such as α-chaconine and α-solanine, which are known to be part of the phytochemical profile of a wide variety of wild Solanum species. This data is consistent with previous findings, which demonstrated that S. bulbocastanum in particular does not contain such compounds [ 21 ] or that if present in its leaves, these metabolites are found in very low quantities [ 19 , 20 , 36 ]. In any case, the presence of such glycoalkaloids in the final extract also depends on the extraction method and solvent used, and thus these results do not exclude the possibility that these Solanaceae -specific glycoalkaloids are found in the leaves of S. bulbocastanum.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The methanolic extract of S. bulbocastanum leaves obtained by the UAE technique did not contain any Solanaceae -specific glycoalkaloids, such as α-chaconine and α-solanine, which are known to be part of the phytochemical profile of a wide variety of wild Solanum species. This data is consistent with previous findings, which demonstrated that S. bulbocastanum in particular does not contain such compounds [ 21 ] or that if present in its leaves, these metabolites are found in very low quantities [ 19 , 20 , 36 ]. In any case, the presence of such glycoalkaloids in the final extract also depends on the extraction method and solvent used, and thus these results do not exclude the possibility that these Solanaceae -specific glycoalkaloids are found in the leaves of S. bulbocastanum.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, in terms of its phytochemical profile, S. bulbocastanum was evaluated only for its glycoalkaloid content and the data available in this regard is somewhat contradictory. While some studies report the presence of both α-chaconine and α-solanine in this species at low concentrations [ 19 , 20 ], others were not able to identify these Solanaceae -specific alkaloids in S. bulbocastanum [ 21 ]. Therefore, considering the lack of knowledge regarding this species and its putative antitumor activity based on results obtained with its phylogenetically close relatives, S. bulbocastanum might have an impact in cancer management, at least in the prevention of cancer due to its usage in potato breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the efficiency of interspecific hybridization for broadening the genetic diversity of S. tuberosum (tbr), protoplast fusion techniques have been frequently used to overcome the interspecific incompatibility between the common potato and the diploid Bgenome Mexican potato species: S. bulbocastanum (blb) [9][10][11][12][13][14][15][16][17], S. pinnatisectum (pnt) [12,13,[18][19][20][21][22][23][24][25][26][27][28], and S. tarnii (trn) [29]; S. cardiophyllum (cph) [23,30,31] and S. x michoacanum (Bitter.) Rydb.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the interspecific somatic hybrids between the potato and diploid B-genome Mexican species had a low level of fertility or were sterile, were characterized by poor agronomic characters, and the degree of their disease and/or pest resistance was lower than in the parental clones of wild species [12,15,17,25,32,34,35]. These undesirable characteristics could be due to somaclonal variation induced during protoplast isolation and fusion and the regeneration of hybrid plants [17,36,37]. Thus, cytogenetic instability as mitotic and meiotic irregularities, aneuploidy, and mixoploidy, were detected using cytological methods in the somatic hybrids tbr(+)blb [12,38,39] and tbr(+)pnt [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation